Nosocomial Severe Bacterial Infection After Cardiac Surgery for Complex Congenital Heart Disease in Heterotaxy Syndrome. Issue 8 (August 2020) - Shao, Pei-Lan; Chen, Meng-Yu; Wu, Mei-Hwan; Wang, Jou-Kou; Huang, Li-Min; Chiu, Shuenn-Nan
Abstract : Background: Patients with heterotaxy syndrome (HS), commonly associated with hyposplenism and complex congenital heart disease (CCHD), require multiple-stage single ventricle type operation for long-term survival. Although a higher risk of community-acquired sepsis and mortality rate was reported in CCHD with HS compared with those without HS, whether the risk of postoperative severe bacterial infection (SBI) is higher in patients with HS remains unknown. Method: All patients with CCHD (with and without HS) born between 2001 and 2013 who received cardiac surgery between 2001 and 2018 were enrolled. We analyzed the epidemiology and risk of postoperative SBI in this CCHD cohort. Result: In total, 101 patients of CCHD with HS and 164 patients without HS were enrolled. The mean postoperative nosocomial SBI rate was 0.73/100 patient-days in patients with HS and 0.56/100 patient-days in patients without HS ( P = 0.13). Multivariate Cox regression analysis demonstrated that the most critical risk factor for postoperative SBI was postoperative intubation >14 days. Preoperative risk factors, including a nonstandard surgical procedure and multiple surgeries, but not HS, were associated with an increased risk of postoperative nosocomial SBI. The pathogens of infection were also similar between these 2 groups. Conclusion: Although commonly associated with hyposplenism, patients with HS have similar postoperative SBI risk and pathogens as those with CCHD alone.